Multi-Omics Revealed Resveratrol and β-Hydroxy-β-methyl Butyric Acid Alone or in Combination Improved the Jejunal Function in Tibetan Sheep - Qiurong Ji; Fengshuo Zhang; Yu Zhang; Quyangangmao Su; Tingli He; Shengzhen Hou; Linsheng Gui (MDPI AG, 2024)
Previous research studies confirmed that both resveratrol (RES) and β-hydroxy-β-methyl butyric acid (HMB) improved growth performance by altering intestinal microbiota. However, the mechanism underlying of RES and HMB on intestinal function remains unclear in ruminant. In this study, supplements of RES and HMB alone or in combination were evaluated as promoters of antioxidant capacity, immune response and barrier function, and modulators of the microbiota and metabolite profiles in the jejunum of Tibetan sheep. A total of 120 two-month-old Tibetan rams were randomly divided into four treatments (n = 30 per treatment), which were supplemented with a basal diet with 1.5 g RES/d (RES group), 1.25 g HMB/d (HMB group), 1.5 g RES/d plus 1.25 g HMB/d (RES-HMB group), and without additions (Control group). The results showed that RES and HMB improved the antioxidant capacity (CAT, GSH-Px, SOD, and T-AOC), immunity (IgA, IgG, and IgM), and digestive enzyme activity (α-amylase, lipase, and chymotrypsin) of the experimental lambs (p < 0.05). Additionally, jejunal morphology including villus width, villus height, and muscle layer thickness exhibited a significant difference when rams were fed diets supplemented with RES and HMB (p < 0.05). Furthermore, the determination of fermentation parameters showed that the butyrate concentration in the RES-HMB group was greater than those in the C and RES groups (p < 0.05). When compared to the C group, barrier-related gene expression (MUC-2, ZO-1, and IL-10) was significantly increased in the RES-HMB group (p < 0.05). Dietary RES and (or) HMB supplementation significantly increased the abundance of Methanobrevibacter, Actinobacteriota and Bacillus (p < 0.05). The abundance of differential bacteria was positively associated with butyrate concentration (p < 0.05). Metabolome analysis revealed that alpha ketoglutarate, succinic semialdehyde, and diacetyl as well as butanoate metabolism pathways connected to the improvements in butyrate concentration by RES and (or) HMB supplementation. Collectively, our results suggested that RES and (or) HMB supplementation improved butyrate concentration via regulating the microbial community (Methanobrevibacter, Actinobacteriota and Bacillus) and metabolism (alpha ketoglutarate, succinic semialdehyde, and diacetyl), thus contributing to jejunal morphology, antioxidant capacity, immune response, digestive enzyme activity, and barrier function.